2022
DOI: 10.22271/oral.2022.v8.i3c.1604
|View full text |Cite
|
Sign up to set email alerts
|

Topical anesthetics in pediatric dentistry: A literature review

Abstract: Introduction: Topical anesthetics are of great interest in pediatric dentistry because they act on the peripheral nerves reducing the sensation of pain when applying local anesthetics. Objective: To analyze the most recent literature on topical anesthetics: benzocaine, lidocaine, eutectic mixture of local anesthetics (EMLA), generalities, doses and presentations, uses and adverse effects. Methodology: Articles on topical anesthetics in pediatric dentistry were analyzed in the databases PubMed, SCOPUS and Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is found that cooling along with topical anesthetic is more effective than topical anesthetic gel alone. 16,17,18,19,20 It can be concluded from the present study that pre-cooling the injection site along with topical local anesthesia is more effective in reducing the pain perception of injection administration compared to topical anesthetic alone. Using ice is effective, cheap and without side effects.…”
Section: Discussionmentioning
confidence: 76%
“…It is found that cooling along with topical anesthetic is more effective than topical anesthetic gel alone. 16,17,18,19,20 It can be concluded from the present study that pre-cooling the injection site along with topical local anesthesia is more effective in reducing the pain perception of injection administration compared to topical anesthetic alone. Using ice is effective, cheap and without side effects.…”
Section: Discussionmentioning
confidence: 76%